Koperasi sebagai Pilar Pemberdayaan Ekonomi dan Sosial: Tinjauan Literatur Sistematis - Fathin Mufid Akram (Fakultas Ekonomi Universitas Advent Indonesia, 2025)
Cooperatives have an important role in improving the economic and social welfare of their members. Through a Systematic Literature Review (SLR) using the PRISMA method, this study found that cooperatives contribute to increased income, access to capital, job creation, and the growth of independent businesses. In addition, cooperatives also strengthen social relations, empower women, expand access to education, and build solidarity in the community. Co-operatives provide a collaborative platform for their members to support each other and share resources to achieve shared prosperity. However, cooperatives still face various challenges, including regulatory constraints, limited access to finance, and low managerial skills in business management. To optimise their role, innovative strategies such as increasing cooperative literacy, utilising digital technology, and actively engaging stakeholders are needed. Thus, cooperatives not only function as economic instruments, but also as key elements in creating sustainable and inclusive social welfare for all their members.